Holographic laser oscillator which adaptively corrects for polarization and phase distortions - Green, R.P.M.; Udaiyan, D.; Crofts, G.J.; Kim, D.H.; Damzen, M.J. (1996)
A solid-state laser resonator is demonstrated which incorporates a real-time holographic element that corrects dynamically for both intracavity phase and polarization distortions. The results are compared with those from a holographic laser which corrects for phase distortions but does not include polarization correction. In comparison to the latter system the polarization correcting laser displays superior performance and notably, an output beam quality and energy that is insensitive to changes in intracavity polarization distortions. ？ 1996 The American Physical Society.